Mitochondrial Genome Fragmentation Unites the Parasitic Lice of Eutherian Mammals. (17th September 2018) - Song, Fan; Li, Hu; Liu, Guo-Hua; Wang, Wei; James, Peter; Colwell, Douglas D; Tran, Anette; Gong, Siyu; Cai, Wanzhi; Shao, Renfu
Abstract: Organelle genome fragmentation has been found in a wide range of eukaryotic lineages; however, its use in phylogenetic reconstruction has not been demonstrated. We explored the use of mitochondrial (mt) genome fragmentation in resolving the controversial suborder-level phylogeny of parasitic lice (order Phthiraptera). There are approximately 5000 species of parasitic lice in four suborders (Amblycera, Ischnocera, Rhynchophthirina, and Anoplura), which infest mammals and birds. The phylogenetic relationships among these suborders are unresolved despite decades of studies. We sequenced the mt genomes of eight species of parasitic lice and compared them with 17 other species of parasitic lice sequenced previously. We found that the typical single-chromosome mt genome is retained in the lice of birds but fragmented into many minichromosomes in the lice of eutherian mammals. The shared derived feature of mt genome fragmentation unites the eutherian mammal lice of Ischnocera (family Trichodectidae) with Anoplura and Rhynchophthirina to the exclusion of the bird lice of Ischnocera (family Philopteridae). The novel clade, namely Mitodivisia, is also supported by phylogenetic analysis of mt genome and cox1 gene sequences. Our results demonstrate, for the first time, that organelle genome fragmentation is informative for resolving controversial high-level phylogenies.